Aromatic Polyphenol π-π Interactions with Superoxide Radicals Contribute to Radical Scavenging and Can Make Polyphenols Mimic Superoxide Dismutase Activity - Francesco Caruso; Sandra Incerpi; Jens Pedersen; Stuart Belli; Sarjit Kaur; Miriam Rossi (Current Issues in Molecular Biology, 2022)
Polyphenols are valuable natural antioxidants present in our diet that likely mitigate aging effects, neurodegenerative conditions, and other diseases. However, because of their poor absorption in the gut and consequent low concentration in biological fluids (µM range), reservations about polyphenol antioxidant efficiency have been raised. In this review, it is shown that after scavenging superoxide radicals, coumarin, chalcone, and flavonoid polyphenols can reform themselves, becoming ready for additional cycles of scavenging, similar to the catalytic cycle in superoxide dismutase (SOD) action. The π-π interaction between one polyphenol ring and superoxide is associated with oxidation of the latter due to transfer of its unpaired electron to a polyphenolic aromatic ring, and consequent formation of a molecule of O2 (one product of SOD action). Mechanistically, it is very difficult to establish if this π-π interaction proceeds before or after the most common mode of scavenging superoxide, e.g., abstraction of an aromatic polyphenol H(hydroxyl), which then is used to form H2O2 (the other molecule produced by SOD action). At the end of this cycle of superoxide scavenging, 4-methyl-7,8-di-hydroxy-coumarin and the flavonoid galangin reform themselves. An alternative mechanistic pathway by galangin forms the η-(H2O2)-galangin-η-O2 complex that includes additional H2O2 and O2 molecules. Another mode of action is seen with the chalcone butein, in which the polyphenol system incorporates a molecule of O2, e.g., a η-O2-butein complex is formed, ready for additional scavenging. Of the several families of polyphenols analyzed in this review, only butein was able to circumvent an initial π-π interaction, directing the superoxide towards H(hydroxyl) in position 4, e.g., acting as a typical polyphenol scavenger of superoxide. This fact did not impede an additional superoxide to later react with the aromatic ring in π-π fashion. It is concluded that by mimicking SOD enzyme action, the low concentration of polyphenols in biological fluids is not a limiting factor for effective scavenging of superoxide.